The Development of Inductive Model in Learning Poetry Appreciation - Warsiman, Warsiman (Institute of Research and Community Service, University of Brawijaya, 2015)
The objective of this research is to improve students’ ability in appreciating poetry through inductive model. Method of research used in this study is modified Research and Development. Data analysis technique that is used is descriptive analysis. The result of research shows that learning through inductive model that concern on eight instructional steps can improve students’ ability in appreciating poetry. The improvement can be seen numerically from evaluation result average in every treatment. In the implementation I, the evaluation result average shows number 60.9, in the implementation II shows number 62.4 and in the implementation III shows number 65.3, while the observation result average in the implementation I from ‘less’ criteria gradually become ‘enough’ criteria, in the implementation II from ‘enough’ criteria gradually become ‘good’ criteria an in the implementation III from ‘good’ criteria gradually become ‘very good’ criteria.Keywords: inductive model, appreciation, poetry, research and development